Interactive teaching in the early school age - Xhemajli, Arbona; Xhemajli, Ardonit (International Journal of Innovative Research and Scientific Studies, 2025)
Innovation in the practice of teaching through interactive models, new roles of teacher and pupil, and the preference for the activity of the pupil in the learning process underlie the changes taking place in education. We are talking about actions that aim to improve the quality, durability, and applicability of the knowledge that pupils acquire in school. So today, in all cycles of education, innovative teaching models are applied that determine the pupil as an active subject in the teaching process. More and more, pupils independently find new information and acquire knowledge. This research highlights the effective realization of the goals set in the educational process, analyzing in detail how much interactive teaching contributes to the improvement of learning results. Specifically, this research examines the impact of interactive teaching on increasing interest in learning, fostering enjoyment and curiosity in children while implementing school curriculum content. The focus of this paper, i.e., this research, is on the teachers from several schools in Kosovo who work in urban areas, pupils from the first grade of Primary School "Selami Hallaci" from Gjilan, and the parents of the pupils of these grades.